2018
DOI: 10.21037/sci.2018.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Notch signalling pathway of cancer stem cells

Abstract: Cancer stem cells (CSCs) have been defined as cells within tumor that possess the capacity to self-renew and to cause the heterogeneous lineages of cancer cells that comprise the tumor. CSCs have been increasingly identified in blood cancer, prostate, ovarian, lung, melanoma, pancreatic, colon, brain and many more malignancies. CSCs have slow growth rate and are resistant to chemotherapy and radiotherapy that lead to the failure of traditional current therapy. Eradicating the CSCs and recurrence, is promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(196 citation statements)
references
References 53 publications
(61 reference statements)
2
178
0
1
Order By: Relevance
“…Notch signalling has been implicated in maintaining tissue homeostasis, including the regulation of self-renewal in adult stem cells, organ development, and embryonic development [200][201][202]. In mammals, the Notch receptor family comprises of four receptors (Notch-1, Notch-2, Notch-3, and Notch-4) and five ligands (Delta-like-1, Delta-like-3, Delta-like-4, Jagged-1, and Jagged-2).…”
Section: Notch Signalling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Notch signalling has been implicated in maintaining tissue homeostasis, including the regulation of self-renewal in adult stem cells, organ development, and embryonic development [200][201][202]. In mammals, the Notch receptor family comprises of four receptors (Notch-1, Notch-2, Notch-3, and Notch-4) and five ligands (Delta-like-1, Delta-like-3, Delta-like-4, Jagged-1, and Jagged-2).…”
Section: Notch Signalling Pathwaymentioning
confidence: 99%
“…The Notch pathway plays a complex role in the tumourigenesis of both hematologic and solid tissues. In fact, Notch signalling plays a vital role in regulating cellular differentiation, angiogenesis, proliferation, and apoptosis [201].…”
Section: Notch Signalling Pathwaymentioning
confidence: 99%
“…CSC‐LCs function rely on their ability to promote the activity of stemness pathways. The genes involved in these pathways are often dysregulated in Oca CSC‐LCs, and are usually integrated into three main clusters involving the WNT/ Β‐ CATENIN/NOTCH network, the MEK/MAPK network and the NANOG/SOX2/OCT4/KLF4 network . Interestingly, in Oca patients with platinum‐resistant tumors, these three pathways were found to be interconnected through a fourth pathway involving C‐KIT, STAT3, NOTCH1 and MYC .…”
Section: Mechanisms Of Platinum Resistance In Ovarian Cancermentioning
confidence: 99%
“…The genes involved in these pathways are often dysregulated in Oca CSC-LCs, and are usually integrated into three main clusters involving the WNT/B-CATENIN/NOTCH network, the MEK/ MAPK network and the NANOG/SOX2/OCT4/KLF4 network. [32,33] Interestingly,i nO ca patients with platinum-resistant tumors, these three pathways were found to be interconnected through af ourth pathway involving C-KIT,S TAT3, NOTCH1 and MYC. [32] This evidence for C-KIT cross-talk with NANOG and OCT4 specifically,issupported by earlier studies which revealed that cisplatin treatment enhances the expression of C-KIT, NANOG and OCT4 in residual ovarian cancerc ells in vitro.…”
Section: Cancerstem Cellsmentioning
confidence: 99%
“…This is consistent with previous observations showing that abnormal expression levels and mutations of genes involved in the cholesterol homeostasis and lipid metabolism are related to cancer 37,38 and OC 39,40 . Likewise, Notch signaling that regulates cell proliferation, stem cell maintenance and that plays a critical role in the cross talk between angiogenesis and CICs self renewal was also an enriched pathway defining the similarity between fresh and scOCOs cells 41 ( fig. 5c).…”
Section: Scocos Highlight Features Related To Hgsoc Ascites That Do Nmentioning
confidence: 99%